Engagements multiples : la rhétorique du GlobalMay Manifesto - Nana Ariel (Argumentation et Analyse du Discours, 2015)
GlobalMay Manifesto, spread on the internet in May 2012, is a collaborative document representing the global Occupy movement, one of few wide-spread international manifestos calling for global democratization, following the global social upheavals of 2011. The manifesto’s attempt to provide a unifying ethos for a fundamentally decentralized and polarized movement was highly criticized, mainly for its vagueness and inconsistency. As opposed to the general evaluative character of the manifesto’s popular and academic readings, this article explores its instrumental strategies for constructing an imagined global collectivity while responding to a wide range of potential requirements and complaints. The hybrid rhetorical structure of the manifesto, its alternating ethos and immanent heteroglossia, are explained as attempts to reconcile clashing attitudes and self-images. This case provides an opportunity to discuss the multilayered nature of the manifesto genre’s rhetoric, specifically the rhetorical challenges it faces in the 21st centur.